Views on the Holying of Stones in Jizzakh Oasis - Shavkatovich, Akchaev Farrux (RA Journal of Applied Research, 2021)
This article analyzes the stone monuments, myths and truths associated with them, which have been considered sacred by the people of the Jizzakh oasis for centuries, based on field research and scientific literature, some rituals and ceremonies performed at the shrines. It is also acknowledged that popular beliefs about shrines and pilgrimages are based on pre-Islamic cult of nature, family, farming, and local cults, as well as totemism, animism, and fetishism, which are part of primitive religious beliefs.